Inverse Static Analysis of Massive Parallel Arrays of Three-State Actuators via Artificial Intelligence - Pasila, Felix <1974> (Alma Mater Studiorum - Università di Bologna, 2013)
Massive parallel robots (MPRs) driven by discrete actuators are force regulated robots that undergo continuous motions despite being commanded through a finite number of states only. Designing a real-time control of such systems requires fast and efficient methods for solving their inverse static analysis (ISA), which is a challenging problem and the subject of this thesis. In particular, five Artificial intelligence methods are proposed to investigate the on-line computation and the generalization error of ISA problem of a class of MPRs featuring three-state force actuators and one degree of revolute motion.